The Improvement of Religion Moderation for Terrorism Prisoner through Islamic Education and Education Character - Sofyan, Ahmad; Lesmana, Johan Aristya; Mustofa, Tutur Ahsanil (CV. Creative Tugu Pena, 2022)
This research focused on the Reeducation stage as the stage of re-loading knowledge about religious education, national education, and character education. The strategy of deradicalization must reach the target of restoration of terrorism prisoners with religious and national principles in accordance with the material provided in reeducation. This study used descriptive qualitative method by conducting in-depth observation on object and subject of the study as primary and secondary data sources. Technique of research analysis used theories and concepts relevant to strategic studies. namely; Strategy Theory, Counter Violent Extremism Concept, Deradicalization Concept, Islamic Education Concept, Character Education Concept, and Religious Moderation Concept. The result of the study on Increasing Religious Moderation among terrorism prisoner must use deradicalization strategy that embeded the values of Islamic Education and National Character Education. Nowadays, there are several agencies that carry out intervention programs including, BNPT, NGO, Religious Instructor, and Correctional Institution. However, the deradicalization program carried out by BNPT is more specific in increasing religious moderation. The strategy of deradicalization in terrorism prisoner in correctional institution through the segmentation of reeducation brought positive contribution to change the attitude of the terrorism prisoner. However, maximum service from the prison remained as the main strategy that is more leverage because the intervention is carried out directly and continuously. Factors that influence positively were the guardian of the military and the strategic policies of correctional institution in providing guidance to the military. The sincere service provided by the civil service as the closest person to the terrorism prisoner is an important factor to change the attitude to be more cooperation. Keywords: Education Character, Religion Moderation, Terrorism Prisoner